Symptoms of Depression, Anxiety and Their Co-Occurrence among Orphaned Children in Sekhukhune District, Limpopo Province - Kebogile Elizabeth Mokwena; Success Magabe; Busisiwe Ntuli (MDPI AG, 2023)
Although both short- and long-term psychological challenges, specifically depression and anxiety, have been reported among orphans, there is a dearth of studies that quantify these disorders in rural settings. The aim of the study was to screen for symptoms of depression, anxiety and their co-occurrence among orphaned school-going children in rural Limpopo province, South Africa. Data were collected among primary school children in 10 schools in two villages in Limpopo province. The Revised Child Anxiety and Depression Scale (RCADS) was used to screen for symptoms of depression, anxiety and their co-occurrence among 308 orphaned learners in the selected schools. A questionnaire was used to collect socio-demographic data. STATA 13 was used to analyse the data. Descriptive statistics were used to determine the symptoms and severity of depression, anxiety and their co-occurrence. The sample of 308 consisted of the majority (60.71%) residing in Maandagshoek and being female (54.22%). Their ages ranged from 8 to 12 years, with a mean of 10.51 years. The prevalence of symptoms of depression, anxiety and co-occurrence of anxiety and depression were 23.05%, 34.09% and 32.14%, respectively. The prevalence of mental health symptoms was high among the sample. There is a need to expand the care of orphans to include mental health and not just limit their care to provide food to vulnerable children.